Evolutionary game analysis of rural public–private partnership older adult care project in the context of population aging in China - Fu, Jianru; Huang, Chao; Li, Shicheng; Xia, Yihan (Frontiers in Public Health, 2023)
Public-private Partnership (PPP) elderly care project is an effective means to solve the dilemma of the aging population in China's rural areas, but there are some problems in the operation process, such as a low participation rate and poor service quality, resulting in the needs of rural elderly groups cannot be met. To alleviate the pressure of the aging population in rural areas, this paper establishes an evolutionary game model for the PPP elderly care project and then defines the interests of local government, private sector, and rural elderly residents, based on which it discusses the strategic choices of the three parties in the evolutionary process, and finally analyzes the influencing factors of the strategic choices of the game parties through simulation. The results suggest that whether the private sector chooses to actively participate in the project will be influenced by the willingness of local government and rural elderly residents to participate in the project; Local government could play the role of supervisor through reward and punishment mechanisms; Whether older rural residents choose to participate in project depends on the number of benefits they would receive. Based on these findings, local government should clarify the responsibilities of relevant stakeholders, adopt a regulatory strategy combining subsidies and penalties, improve the participation efficiency of rural elderly residents, promote the effective operation of PPP elderly care project, and improve the quality of rural elderly care services in the new era.